2011
DOI: 10.1093/jac/dkr507
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extended-spectrum cephalosporinase (ESC)-producing Escherichia coli in Danish slaughter pigs and retail meat identified by selective enrichment and association with cephalosporin usage

Abstract: The usage of cephalosporins for slaughter pigs may increase the prevalence of ESC E. coli in slaughter pigs. Meat may be a source of ESCs in humans, especially imported broiler meat. Selective enrichment should be considered as a supplementary surveillance method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 25 publications
5
70
1
Order By: Relevance
“…The use of broad-spectrum veterinary cephalosporins (especially "third-generation" and "fourth-generation" cephalosporins, such as ceftiofur and cefquinome) has been proposed as an important reason for the occurrence of these bacteria among food-producing animals and meat products (6). In Denmark, the consumption of cephalosporins in pigs increased from 2001 through July 2010, when the pig industry decided to ban their use (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of broad-spectrum veterinary cephalosporins (especially "third-generation" and "fourth-generation" cephalosporins, such as ceftiofur and cefquinome) has been proposed as an important reason for the occurrence of these bacteria among food-producing animals and meat products (6). In Denmark, the consumption of cephalosporins in pigs increased from 2001 through July 2010, when the pig industry decided to ban their use (26).…”
Section: Discussionmentioning
confidence: 99%
“…CTX-M-1 is the most frequently reported ESBL type in food animals in Europe, and this was also the first type discovered in Danish pigs in 2005 (5). The same type was also predominant in a recent study of pigs at slaughter in Denmark, followed by CTX-M-14, CTX-M-2, and CTX-M-15 (6). In Europe, CTX-M-1 and CTX-M-14 have also been detected among pigs in Spain, France, the United Kingdom, and Switzerland (7)(8)(9)(10)(11)).…”
mentioning
confidence: 86%
“…In addition, the results also showed that the overall prevalence of ESBL-E. coli is higher in Thai Binh than in Nha Trang. A study conducted in Denmark reported that 36 % of samples from imported broiler chicken were contaminated with extendedspectrum cephalosporinase-producing E. coli (Agersø et al 2012), while a similar study conducted in the Netherlands showed that 76.8-94 % of poultry products were contaminated with ESBL-E. coli (Leverstein-van Hall et al 2011; Overdevest et al 2011). Thus, the prevalence of ESBLproducing bacteria in food products varies in different geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Asia and Europe, ESC resistance in E. coli isolated from livestock has been attributed to the emergence and spread of plasmidmediated bla CTX-M genes and bla CMY-2 [6][7][8]. In several countries in these regions, extensive use of FQs in some food-animal species has been linked to the emergence of FQ-resistant E. coli and Salmonella [9,10].…”
Section: Plasmid-mediated Esc Resistance (Mediated By Bla Cmy-2 ) Wasmentioning
confidence: 99%